Considerations to Rearrange the Value Chain - Hofbauer, Günter; Sangl, Anita (Archives of Business Research, 2018)
Purpose of the article: The basic research question of this paper is to consider how to rearrange the value chain after having served 35 years as a helpful management concept. The primary activities are revised and will be rearranged after careful considerations. Methodology: This scientific approach is analytical and conceptual. First, we derive on the analytical basis of statistical data the relevance for value creation. Second, the theoretical and conceptual approach is providing a systematic overview on the activities under research of a contemporary value driven company. Scientific aim: The scientific aim of this article is about rethinking of the primary activities of the value chain. The requirement of integrating a new activity and taking out another primary activity is explained and based on analytical and conceptual considerations. Findings: Organizations, processes and business models are changing rapidly. This leads to changes in business operations on a large scale. Procurement for example is not any more just the supporting ordering department. Procurement has changed into a value creator. On the other side logistic activities should not be regarded as primary activities anymore, because there is no value added by inbound nor outbound logistics. Conclusions: This article reconsiders the value chain under contemporary conditions in the age of Industry 4.0 to achieve competitive advantage. The first conclusion is to consider procurement not any more as a secondary activity, but as a primary activity, because procurement has the highest impact on the cost position of a product. The second conclusion is that the logistic activities were identified not to be regarded as a primary activitie any more. They should be integrated into the secondary activities, because the value add is insignificant.